La poétique du bateau dans la fiction mauricienne - Namrata Poddar (Itinéraires)
Since antiquity, boats have been invested with a literary imaginary as the medium for travel and the discovery of the unknown—a phenomena particularly conspicuous in the Western (exoticist, modernist and post-modemist) literary tradition. One may then speak of a poetics of the boat that foregrounds the narrative of glorious and perilous sea-voyages, geographical discoveries, trade, war, colonization; or of positive transformations and pluralist processes. This article will examine the various representations of the boat in five contemporary Mauritian novels, the ways in which they destabilize a prevalent, celebratory poetics of the boat in orderfinally to suggest the singularity of the Mauritian poetics of the boat.